2016
DOI: 10.1186/s12931-016-0452-2
|View full text |Cite
|
Sign up to set email alerts
|

Sirt1 expression is associated with CD31 expression in blood cells from patients with chronic obstructive pulmonary disease

Abstract: BackgroundCigarette smoke induced oxidative stress has been shown to reduce silent information regulator 1 (Sirt1) levels in lung tissue from smokers and patients with COPD patients. Sirt1 is known to inhibit endothelial senescence and may play a protective role in vascular cells. Endothelial progenitor cells (EPCs) are mobilized into circulation under various pathophysiological conditions, and are thought to play an important role in tissue repair in chronic obstructive lung disease (COPD). Therefore, Sirt1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 56 publications
1
15
0
1
Order By: Relevance
“…A recent study including 358 patients with a smoking history of >10 pack-years showed decreased SIRT1 mRNA levels and number of EPCs (85).…”
Section: Sirt1 In Cell Senescence and Aging Processesmentioning
confidence: 96%
“…A recent study including 358 patients with a smoking history of >10 pack-years showed decreased SIRT1 mRNA levels and number of EPCs (85).…”
Section: Sirt1 In Cell Senescence and Aging Processesmentioning
confidence: 96%
“…Mechanistic studies show that silent information regulator 1 (SIRT1) is involved in the pathogenesis of COPD, with decreased levels in bronchial epithelial cells (Beas-2B) and mouse lungs exposed to cigarette smoke extract (CSE), as well as in the lungs and blood cells of COPD patients. 9 , 10 SIRT1 belongs to the class III histone/protein deacetylases, which possess anti-inflammatory, anti-aging/senescence properties. 9 , 11 SIRT1-mediated protection in response to CSE-induced lung inflammatory response and injury is linked to the activation of nuclear factor-κB (NF-κB)/p65.…”
Section: Introductionmentioning
confidence: 99%
“…Endothelial progenitor cells (EPCs) have been studied in COPD patients' blood. Also here, downregulation of some genes such as Sirt1 mRNAs, CD31, CD34, and miR-126-3p emerged clearly, while the overexpression of miR-34a was observed only in comparison with signals from healthy smokers [92]. Remarkably, Sirt1 protein and its fragments has been found in COPD serum [93].…”
Section: The Involvement Of Sirtuins In Other Pathophysiological Condmentioning
confidence: 58%
“…Specifically, Sirt1 120KDa (S120) has been found fragmented in COPD patients compared with healthy smokers or non-smokers subjects [93]. All of these observations suggest the possibility to use CD31, CD34, Sirt1 mRNAs, miR-126-3p, miR-34a [92] and S120 [93] as biomarkers for a better detailed diagnosis of COPD.…”
Section: The Involvement Of Sirtuins In Other Pathophysiological Condmentioning
confidence: 91%